Cyclic β-glucans at the bacteria–host cells interphase: One sugar ring to rule them all - Guidolin, Leticia Soledad; Arce Gorvel, Vilma; Ciocchini, Andres Eduardo; Comerci, Diego José; Gorvel, Jean-Pierre (Wiley Blackwell Publishing, Inc, 2018)
Fil: Guidolin, Leticia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Instituto de Investigaciones Biotecnológicas. Universidad Nacional de San Martín. Instituto de Investigaciones Biotecnológicas; Argentina